Disruptive effects of faulting on shale gas preservation in Upper Yangtze region - Guangchun YU; Xiangfeng WEI; Fei LI; Zhujiang LIU (Shiyou shiyan dizhi, 2020)
The fracturing of the Paleozoic marine shale in the Sichuan Basin and its periphery was studied. The disruptive effects of faulting on shale gas preservation were analyzed based on the comprehensive interpretation of seismic structure, the analysis of fluid inclusions in calcite veins in fractures in shale layers, and the consideration of typical shale gas wells with different gas-bearing properties. Fault level, spatial stacking pattern, stage and duration have an important influence on the preservation conditions of shale gas. (1) The higher the fault level is, the larger the impact. The preservation conditions for shale gas are destroyed in the areas close to the first-level faults (within about 10 km), the second-level faults (within about 5 km), and the third-level faults (within about 2-3 km), but not influenced in the area close to the fourth-level faults. (2) Under the premise of similar fracture density in the well area, when different levels of faults intersect from parallel or small angles to large angles, the damage to shale gas preservation gradually increases. (3) The more fault activity periods and the longer their duration, the greater is the damage to shale gas preservation in the later period. Fault period and activity duration can be divided into 4 types: (1) short-term activity in the late Yanshan period, whose impact on preservation conditions was small; (2) intermittent activity in the Yanshan and early Himalayan periods where preservation conditions were affected to some extent; (3) continuous activity since the late Yanshan period, which caused serious damage to preservation conditions; and (4) continuous activity since the Himalayan period, which had a greater impact on preservation conditions.